Expatriate adjustment in Portugal: A counterintuitive experience? - Coelho, J. V. (XI Congresso Português de Sociologia, 2021)
Expatriation has been subject to divergent representations as an employment practice increasingly associated and used to anchor the expansion of transnational productive activities. This divergent, two-folded representation is framed, on the one hand, by managerial perspectives that portray expatriation as a valuable resource lacking negative consequences and as a chance to enhance one’s personal, family and professional future. In sharp contrast, other studies portray expatriation as an ambiguous work arrangement that may imply conflictive and contradictory consequences, and which can spark feelings of rupture with regard to one’s personal, professional, and family past trajectory and future plans.This presentation aims to report the results of a PhD study, where expatriation was taken as empirical reference to enquiry contemporary transnational work and employment practices implications. This study found that being an expatriate often implies work and life situations that are subject to diffluent reasoning, a circumstance primarily associated with the objective attributes used to characterize and mold expatriation as a contemporary employment practice and work setting.In this regard, six attributes are presented as constituting differential operators used by expatriates to position their expatriation work experiences, to position themselves with regards to these (their) experiences, and to present expatriation as a counterintuitive work and life condition: a sense of periodization and cyclical nature; the remote likelihood of returning to one’s place of origin; difficulties in finding a suitable work-life balance; the rarefaction of preexisting social bonds; exposure to organizational rules and decisions lability; exposure to feelings of distance, uprooting and displacement.